Implementation in Indonesia of the WHO Pocket Book of Hospital Care for Children. (May 2014) - Li, Michelle Y.; Puspita, Ratih; Duke, Trevor; Agung, Fransisca H.; Hegar, Badriul; Pritasari, Kirana; Weber, Martin W.
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Effective implementation of evidence-based practice guidelines has the potential to improve quality of hospital care for children. To achieve this in Indonesia, a locally adapted version of the WHO Pocket Book of Hospital Care for Children was published in 2009. Objectives: To document implementation of the Pocket Book in Indonesia and to compare uptake in health facilities in which there has been a quality-improvement approach involving audit and feedback with uptake in settings in which there has been only passive dissemination. Methods: Indonesian district health offices, district hospitals, health centres with beds, and medical schools were surveyed by telephone, and an online and telephone survey of paediatricians was conducted. Health facilities in four provinces were visited, and key stakeholders were interviewed. Health facilities were assessed on availability of the guidelines, use by staff, and their incorporation into hospital procedures and activities. Results: There was evidence of use of the Pocket Book across Indonesia, despite limited funding for implementation. Its distribution had reached all provinces; 61% (33/54) of health facilities surveyed had a copy of the guidelines. Hospitals involved in a related quality audit were more likely to report use of the guidelines than hospitals exposed to passive dissemination, although this difference was not significant. Of 150 paediatricians sampled, 109 (73%) reported referring to the guidelines in their clinical practice. The guidelines have been incorporated into the postgraduate paediatric curriculum in four of 13 universities sampled. Conclusion: There was encouraging evidence of uptake of the Pocket Book in Indonesia following local adaptation, nationwide mailing distribution and small-scale local implementation activities.